Analysis of high risk pregnancies in the region of Rimavská Sobota - Mária Šupínová; Gabriela Sonkolyová (University of Ostrava, 2018)
Aim: The analysis high-risk pregnancy, in order to determine what demographic and other factors are most commonly reported in women with high-risk pregnancy, and what relationships are among the variables recorded. Design: The method used was a retrospective observational study of cases. Methods: The study included 1,256 women at the Rimavská Sobota obstetrics and gynaecological unit hospitalized with a high-risk pregnancy in the two years. The method used was a retrospective observational study of cases. For processing were used statistic methods. Results: The average age of the sample was 24.45 years. 584 respondents (46.50%) were without education. 316 respondents (25.16%) did not go to prenatal counselling at all, or irregularly. The most significant dependences were demonstrated within the following variables - between the time of onset of respondentsʼ problems and the presence of associated diseases, the time of onset of the problems and the number of spontaneous abortions suffered in the past, between termination of current pregnancy by abortion in respondents and prenatal counselling visits and between termination of current pregnancy by abortion and previous high-risk pregnancies. Conclusion: The results of the study confirmed the importance of prenatal care for women during pregnancy. Effective education focusing on reproductive health for girls of school-age, implemented by nurses, could also help to solve the problems identified. Keywords: birth, complications, high risk pregnancy, prenatal counselling, risk factors.